Generationen, Generationenbeziehungen, Generationenpolitik: ein mehrsprachiges Kompendium - Kurt Lüscher; Andreas Hoff; Giovanni Lamura; Marta Renzi; Mariano Sánchez; Gil Viry; Eric Widmer; Andrzej Klimczuk; Paulo de Salles Oliveira (Universität Konstanz, 2014)
The members of the International Network for the Analysis of Intergenerational Relations (Generationes) proudly present the most recent issue of the jointly produced compendium “Generations, Intergenerational Relations and Generational Policy”. This new version includes seven languages (English, French, German, Italian, Spanish, Polish (New) and Portuguese (New)). Its layout is designed for using it to translate the specific concepts and terminology of research into generations and intergenerational relations from one language into another.
Keywords: J14; J18; Z18; 330; generation; Intergenerational relations; ageing; demography; Gerontology; Aging population